PELATIHAN PEMBUATAN GAME EDUKASI SEDERHANA UNTUK MENINGKATKAN KREATIVITAS SISWA SMP - Rahman, Muhammad Saidi; Indra Wijaya, Yusup; Hoiriyah, Hoiriyah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This community service program aims to enhance the digital creativity of junior high school students through training in developing simple educational games. Based on the needs analysis at the partner school, it was found that 85% of students had a high interest in games but lacked the skills to create them productively. This program offers a comprehensive solution through: (1) intensive project-based training using the beginner-friendly Scratch platform, (2) strengthening the capacity of ICT teachers as sustainable facilitators, (3) establishing a creative digital learning community at the school, and (4) optimizing supporting infrastructure. The implementation method applies a learning-by-doing approach, in which each student group develops an educational game prototype aligned with curriculum themes. This program not only focuses on the technical aspects of game development but also fosters a sustainable digital creativity ecosystem through collaboration with teachers and the establishment of a school-based game development club. It is expected that this program can serve as a model for technology-based creativity development that is easily replicable in other schools with similar characteristics.